Flexural and impact properties of kenaf-glass hybrid composite - Maleque, Md. Abdul; Afdzaluddin, Atiqah; M., Iqbal (Trans Tech Publications, Switzerland, 2012)
This paper investigates the flexural and impact properties of kenaf-glass (KG) fibers reinforced unsaturated polyester (UPE) hybrid composite on a source of green composite. The matrix is kept constant with 70 % volume fraction while kenaf and glass fibers were varied, such as 7.5/22.5 v/v, 15/15 v/v and 22.5/7.5 v/v. The 30 % kenaf and 30 % glass are also used for the preparation of composite materials. The kenaf fiber was treated with 6% sodium hydroxide (NaOH) diluted solution for 3 hours. Hybrid composites are fabricated using sheet molding compound (SMC) process. The mechanical tests, such as flexural and impact are performed using ASTM D790-03 and ASTM D256-04 respectively. The study showed that the highest flexural strength was obtained from treated kenaf with 15/15 v/v KG fiber reinforced hybrid composite while untreated of 15/15 v/v KG composite showed the highest value of impact strength in this investigation. This can be concluded that 15/15 v/v KG fiber reinforced unsaturated polyester hybrid composite is the most appropriate hybrid composite which can be considered for many engineering structural applications, such as automotive, aerospace, construction or sports.